Dependency of biological contaminants on temperature and relative humidity within praying halls of mosques - Nur Baitul Izati Rasli,; Nor Azam Ramli,; Mohd Rodzi Ismail,; Syabiha Shith, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The widespread use of Air Conditioning Split Units (ACSU) to cool the air inside mosques may pose potential adverse health effects, secondary to exposure to biological contaminants. To address this issue, the dependencies of biological contaminants (bacteria and fungi) on temperature (T) and relative humidity (RH) of the ‘mosques’ indoor air were evaluated. A total of 25 mosques were investigated during the periods in which their respective congregators were performing Zohor or Friday, and Asar prayers. The recorded average indoor bacteria and fungi concentrations were 382.6±143.9 cfu/m3 and 229.4±165.5 cfu/m3, respectively. However, the study found that masses of bacteria aerosol within the indoors of certain mosques (10 out of 17 ACSU mosques and 1 out of 8 non-ACSU mosques) exceeded the limit recommended by Malaysian standard for indoor air quality (500 cfu/m3). Meanwhile, the results of regression analyses suggested that T and RH of the indoor air have high influence on airborne bacteria and fungi. The variations in bacteria concentrations due to the influence of T and RH in ACSU mosques (T= 92.3%; RH= 90.3%) were higher than in non-ACSU mosques (T= 82.75%; RH= 81.7%) whereas the variations in fungi concentrations in non-ACSU mosques (T=70.45%; RH= 71.45%) were higher than in ACSU mosques (T= 66.05%; RH= 60.7%). This research shows that the growth of bacteria and fungi within the prayer halls of mosques in Malaysia is very much dependent on its indoor T and RH.